A method for improving the efficiency of DNA extraction from clotted blood samples. Issue 6 (10th May 2019) - Mardan‐Nik, Maryam; Saffar Soflaei, Sara; Biabangard‐Zak, Atefeh; Asghari, Mahla; Saljoughian, Sania; Tajbakhsh, Amir; Meshkat, Zahra; Ferns, Gordon A.; Pasdar, Alireza; Ghayour‐Mobarhan, Majid
Abstract : Background: The efficient and rapid extraction of high‐quality genomic DNA from clotted blood samples, which normally have a low yield and poor quality, is an important factor in genomic research. The objective of this study was to develop a simple and safe technique for dispersing the blood clots by the ball bearing metal shots. Normally, such clot samples may not have an acceptable yield by conventional DNA extraction methods. Also, in the present study, we have further investigated to improve salting‐out DNA extraction methods. Methods: Initially, 500 µL phosphate‐buffered saline (PBS) (1×) and two ball bearing metal shots were added to each tube of the clotted blood sample and then were gently rotated in an electric laboratory rotator for 1 hour at room temperature (18‐25°C). Genomic DNA was then extracted from samples using a modified salting‐out method and a modified QIAamp ® DNA Blood Midi Kit and was compared with QIAamp ® DNA Blood Midi Kit as a control. An assessment of the concentration and quality of the extracted DNA was performed using the UV‐visible spectrophotometer. The isolated DNA proved amenable to PCR amplification and gel electrophoresis. Results: The yield and purity of DNA obtained by these three methods were significantly different ( P < 0.001), with a higher yield in the modified salting‐out method. Conclusions: Our proposed modified salting‐out method is simple and efficient for the isolation of DNA from old blood clot samples. It is both easy to use and is of low cost in routine laboratory tasks.